Personal control related to childbirth satisfaction among postpartum mothers in Hospital Tengku Ampuan Afzan (HTAA) - Mohd Arifin, Siti Roshaidai; Addenan, Nor Ashikin (2013)

(untitled)
Background: The experience of childbirth is one of the most momentous events in a woman’s life, remembered with great clarity and emotion decades later. Either in positive or negative perceptions, the experience of childbirth assumes a single meaning for each woman. Controlling emotions and actions during childbirth process had a positive impact on childbirth satisfaction for mothers. Question: Is there any relationship between personal control and childbirth satisfaction among post-partum mothers? Methods: This is a cross-sectional study using convenience sampling conducted on 102 post-partum mothers who delivered their baby through spontaneous vagina delivery at a government hospital located in the East Coast Region of Peninsular Malaysia. Labour Agency Scale and Mackey childbirth satisfaction were used to measure personal control and childbirth satisfaction, respectively. The data has been analyzed by using Portable Analysis Statistics Windows (PASW) version 18. Descriptive statistics were used to measure the personal control and childbirth satisfaction. Correlation test and t-test were used to test the relationship of socio demographic data with personal control and chidlbirth satisfaction. Findings: The mean score for personal control among postnatal mother was 52.56 [SD = 10.693, min max (29, 70)] with the mean childbirth satisfaction score of 140.06 [SD = 17.109, min max (89, 170)]. There was significant association between personal control and chilbirth satisfaction (r = .373, p = 0.00). Conclusion: Mothers who achieved high score in personal control experienced positive childbirth satisfaction. The laboring mother should be fully supported in order to improve their childbirth satisfaction.